Strategi Digital Marketing dalam Meningkatkan Efektivitas Media di IDN Boarding School - Fadlan, Muhammad; Putra, Mohammad Royger Febriansyah; Khanif, Abror; Iskandar, Dadang Mulyana (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
In the era of the Industrial Revolution 4.0, digital marketing strategies are essential. Therefore, the author aims to enhance the effectiveness of digital marketing strategies at the IDN Boarding School Jonggol Media Team, with the output being a web-based application. The main issues identified include a lack of structure in workflows, delays in task execution, and irregularities in progress reporting. Utilizing the Waterfall model of the Software Development Life Cycle (SDLC), the application is designed to manage task distribution, monitor progress in real-time, and ensure consistency in content publication across various social media platforms such as Instagram, YouTube, TikTok, and the school's official website. Data collection methods include observation, interviews with the Media Team Coordinator, and literature studies. The implementation results demonstrate that the application successfully improves transparency, collaboration efficiency, and reporting accuracy, thereby supporting the optimization of digital marketing strategies. This research provides a relevant technological solution to support media team task management and enhance the competitiveness of educational institutions in attracting public interest.